Correlation of head and shoulder posture with non-specific neck pain: A cross-sectional study - Battecha, Kadrya H; Salaheldein Alayat, Mohamed; Mousa, Gihan Samir; H M, Mahmoud; Thabet, Ali A. El-monsif; Ebid, Anwar A.; Ibrahim Salem, Mohamed Mohamed; Alharbi, Albatol B.; Batawi, Ghaidaa W.; Almurakshi, Danah M.; et al. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Non-specific neck pain (NSNP) is one of the most significant health problems especially with frequent use of media devices as computers and cell phones that may be associated with some faulty postures as forward head posture or rounded shoulders. The aim of this study was to investigate the relation of neck, head and shoulders angles: cranio-cervical angle (CVA), forward shoulder angle (FSA), coronal shoulder angle (CSA) and sagittal head tilt angle (SHT) with the non-specific neck pain. A total of ‏ 100 females with non-specific neck pain, whose ages were ranged between 18-25 years old. Numeric Pain Rating Scale (NPRS) and Digital Camera were used to assess neck pain, and neck different angles of cervical and shoulders, respectively. There was indicated a positive and significant correlation between NPRS and FSA (P < 0.045), while there were non-significant correlations between NPRS and other variables (P > 0.05). It was found that there was a significant positive correlation between forward shoulder angle and non-specific neck pain in the sample of female participants. However, no significant associations were observed between neck pain intensity and CCA, CSA, and SHT. Addressing and improving forward shoulder angles may be a potential strategy to reduce neck pain in individuals with non-specific neck pain.